Design and Implementation of Directional Sensors for Privacy-Ensured Device-Free Target Localization in Indoor Environment - Rehman, Ata ur; Ellahi, Zeeshan; Iqbal, Asif; Ullah, Farman; Ali, Ahmed; Kwak, Kyung Sup (Wireless Communications and Mobile Computing, 2019)
This paper presents two radio frequency (RF) sensors with different directivities designed and tested for device-free localization (DFL) in an indoor environment. Mostly, in smart homes and smart offices, peoples may be irritated by wearing the device on them all the time. As compared with device-based localization, the proposed sensors can localize both cooperative and non-cooperative targets (intruders and guests etc.) without privacy leakages. Both sensors are tested to detect the change in received signal strength (ΔRSS) due to the presence of an obstacle. RF sensors, i.e., antennas are designed to operate in the ISM band of 2.4–2.5 GHz. Experimental results show that the sensor with higher directivity provides better ΔRSS that helps in improved accuracy to detect a device-free target.